2023
DOI: 10.33192/smj.v75i3.260869
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Metabolic Syndrome and Its Associated Factors Among Thai Police Officers – A Population-Based Study

Abstract: Objective: The prevalence of Metabolic Syndrome (MetS) in Thai police officers is unknown. This study aims to accurately determine the prevalence of MetS in this population compared to the Thai general population. Materials and Methods: We conducted a population-based cross-sectional study of 107,933 Thai police officers during the 2012 annual Police Health Care Center check-up. Metabolic syndrome was defined using the harmonized criteria of six international expert groups. Results: The prevalence of MetS amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Police personnel reportedly have a high prevalence of hypertension and MetS, which further contributes to their health deterioration and unavailability for duty ( Yates et al, 2021 ). Recent studies conducted in Thailand have shown that law enforcement officers have a higher prevalence of MetS compared to the general population, with rising rates of overweight or obesity and associated hypertension among military personnel ( Gurung et al, 2023 ; Napradit et al, 2007 ). Hence, prioritizing the health and well-being of law enforcement officers is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Police personnel reportedly have a high prevalence of hypertension and MetS, which further contributes to their health deterioration and unavailability for duty ( Yates et al, 2021 ). Recent studies conducted in Thailand have shown that law enforcement officers have a higher prevalence of MetS compared to the general population, with rising rates of overweight or obesity and associated hypertension among military personnel ( Gurung et al, 2023 ; Napradit et al, 2007 ). Hence, prioritizing the health and well-being of law enforcement officers is crucial.…”
Section: Introductionmentioning
confidence: 99%